Tailored high performance shape memory epoxy–silica nanocomposites. Structure design. Issue 3 (20th November 2015) - Ponyrko, S.; Donato, R. K.; Matějka, L.
Abstract : The shape memory (SM) properties of polymers depend on material toughness and the efficiency of SM performance is governed by morphology and viscoelasticity. Abstract : High performance shape memory (SM) epoxy–silica nanocomposites have been synthesized. The structure of the corresponding SM polymer was designed on the basis of the determined relationships between structure, mechanical properties and SM performance. The recovery stress, as a crucial SM property of high performance systems, is governed by the material toughness while the efficiency of the SM performance is controlled by morphological homogeneity and viscoelastic behaviour of the polymer as well as by experimental conditions of the SM procedure. The nanocomposites were prepared by in situ generation of nanosilica in the epoxy matrix. A non-aqueous sol–gel procedure was applied and the ionic liquid (IL) was used in the synthesis as a multifunctional agent controlling morphology and mechanical properties. The effect of nanosilica, IL, crosslinking density of the epoxy network, physical crosslinking as well as the application of the concept of bimodal networks on SM performance was evaluated and discussed. Based on the knowledge of the corresponding relationships and structural effects the SM nanocomposite was synthesized showing the high recovery stress σ r = 3.9 MPa or high deformability ε b = 103%. The study contributed to the better understanding of the SM behaviour of polymers.